Short communication: Laboratory approach to the use of sulphur and kaolin as preventive control against Drosophila suzukii - Pérez-Guerrero, Sergio; Molina, José M. (Spanish Journal of Agricultural Research, 2016)
Drosophila suzukii (Matsumura, 1931) is an invasive pest from South East Asia that was detected for the first time in Southern Europe in 2008. This species can damage a wide range of soft-skinned fruits crops affecting ripening fruits and causing important economic losses. Since the exclusive use of chemical insecticides for controlling D. suzukii may prompt the appearance of resistance and environmental pollution, alternative methods compatible with sustainable management are required. In this study, commercial formulations of powdered sulphur and kaolin were tested as a preventive method applied to blueberry fruits under laboratory conditions. In no-choice assay, powdered sulphur had a significant effect on oviposition and adult emergency with reductions of 76% and 77%, respectively. In addition, sulphur displayed a significant toxicity on males and lethal effect with over 40% adult mortality seven days after exposure. The choice assay confirmed and improved the powdered sulphur effects, with reductions of 98% and 96% in oviposition and adult emergence, respectively. In contrast, kaolin produced no significant reduction in infestation and adult mortality during no-choice and choice assays. These outcomes suggest that preventive use of powdered sulphur could be considered for sustainable control of D. suzukii in some berry crops.